The Crusades: Causes and Impact - Sandi, Susandi; Alfisyah, Nandalifia; Yuhani (Yayasan Tahfidzul Qur'an Al-Fawwaz, 2024)
The Crusades were triggered by the occupation of several Christian cities and holy sites by Islam in 632 AD. The Christian military used the cross as a symbol to signify that the war had a holy purpose, namely to liberate the holy city of Jerusalem from Islamic rule. To ensure the war was deemed truly sacred, all Western fleets and troops participating in the war were required to wear the cross emblem, such as on sail flags, team and troop banners, shields, armor, and other equipment. This study is a literature review. The approach applied in this research is qualitative. Primary data sources come from supportive references, while secondary data sources involve several journals and books. Data analysis is conducted using the content analysis method. The research findings indicate that the Crusades originated from European expansionism in response to the actions of the Seljuq Turks against the Byzantine Empire. Several factors contribute to the occurrence of the Crusades, including religious, political, social, and economic factors. The Crusades have significant impacts on both the Islamic and Western worlds.